2020
DOI: 10.1111/sum.12611
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on biosorption and biogenic calcite precipitation in sands

Abstract: Natural soil deposits may require modifications to meet the desired shear strength, reduced permeability and liquefaction potential, for the safety of infrastructure projects. In order to achieve this, conventionally, several physical and chemical treatments have been practiced (Ou et al., 1996;Zayyat et al., 2005). Among these, physical methods like heavy tamping or vibratory methods might pose a serious threat to the nearby structures, especially in the urban landscapes, due to an increase in the pore-water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The characterization of MICP at multi‐scales ((a) SEM images of precipitation (Xu et al, 2020); (b) AFM peak‐force error images of substrates with bacteria cell adhesion (Shashank et al, 2020); (c) the particle‐scale behaviour of calcite precipitation from a microfluidic chip (Wang et al, 2019a); (d) the XRD patterns of CaCO 3 crystals (Wen et al, 2020); (e) shear response of bio‐cemented sand by undrained triaxial test (Nafisi et al, 2019); (f) the unconfined compress (UCS) test (Fang et al, 2020); (g) one‐dimensional compression test (Xiao, Chen, et al, 2020a); (h) predicted volume fractions of final calcite by numerical modelling (Hommel et al, 2020); (i) seismic shear‐wave data of 100‐m 3 large‐scale bio‐grouting test (Van Paassen et al, 2010a; Van Paassen et al, 2010b); (j) dynamic cone penetration (DCP) data of field‐scale test measuring 2.4 m × 4.9 m on loose sand (Gomez et al, 2015); (k) Five‐Spot treatment model (Dejong et al, 2014))…”
Section: Characterization Of Micp Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of MICP at multi‐scales ((a) SEM images of precipitation (Xu et al, 2020); (b) AFM peak‐force error images of substrates with bacteria cell adhesion (Shashank et al, 2020); (c) the particle‐scale behaviour of calcite precipitation from a microfluidic chip (Wang et al, 2019a); (d) the XRD patterns of CaCO 3 crystals (Wen et al, 2020); (e) shear response of bio‐cemented sand by undrained triaxial test (Nafisi et al, 2019); (f) the unconfined compress (UCS) test (Fang et al, 2020); (g) one‐dimensional compression test (Xiao, Chen, et al, 2020a); (h) predicted volume fractions of final calcite by numerical modelling (Hommel et al, 2020); (i) seismic shear‐wave data of 100‐m 3 large‐scale bio‐grouting test (Van Paassen et al, 2010a; Van Paassen et al, 2010b); (j) dynamic cone penetration (DCP) data of field‐scale test measuring 2.4 m × 4.9 m on loose sand (Gomez et al, 2015); (k) Five‐Spot treatment model (Dejong et al, 2014))…”
Section: Characterization Of Micp Processesmentioning
confidence: 99%
“…Atomic force microscopy (AFM) developed in 1986 is an ideal tool which can be applied to acquire the surface topography and texture information with demonstrated resolution on the nanometre scale. Shashank et al (2020) used AFM to investigate the capability of the biosorption of bacteria on the surface of soil particles. They found that the extent of bacterial adhesion on soils depends on the available hydrophobic binding sites, and bacteria could be entrapped in the pores of formed crystals based on the surface texture parameters during the MICP treatment.…”
Section: Characterization Of Micp Processesmentioning
confidence: 99%